Interdisciplinary treatment of eco-sustainability in Secondary Education: A case study - Vázquez Cano, Esteban (Profesorado, Revista de Currículum y Formación del Profesorado, 2012)
This paper presents and analyzes a research on new approaches to develop environmental education from interdisciplinary projects involving a large number of students and faculty in schools. The project discussed is called: "Awareness and school´s abiotic resource management." This project was developed in a secondary school in the province of Toledo and pursues an interdisciplinary collective construction of knowledge and environmental awareness starting from the basic elements of the curriculum: objectives, competencies and contents. Project development has been characterized by their adaptability to the context and development of practical attitudes towards sustainability, recycling, and saving energy. For the analysis we designed a qualitative and quantitative methodology which allowed us to observe the high functionality and usefulness of this type of project in achieving the goal of generating in students attitudes and behaviors for the sustainable eco-mediate environment.